See-through mobile augmented reality on iPad/iPhone - Gong, Ji Yi. (2012)
The purpose of this project is to develop augmented reality (AR) applications on specific platforms, such as mobile devices (cellphone/tablet) or micro-projector/camera systems. Using these platforms, we will then investigate human-computer interactions, specifically to understand how different users (with different abilities) can benefit from augmented reality tools in various applications, and in using these findings to improve the user experience in AR applications and environments. The project was started from stretch including development platform selection, mobile device selection, SDK selection, and biomedical image data selection. I have implemented the application through the Qualcomm AR Software Development Kit (SDK) via Eclipse and Unity 3D. Firstly, chapter 1 gives detail background information of the AR market and application field, followed by the literature reviews in chapter 2. Chapter 3 explains how the first step of the project was implemented using Qualcomm AR via Eclipse. Chapter 4 explains how the Unity feature enhanced the visual effect of the project. Chapter 5 concludes the work, the difficulties that met during the project implementation and the future development for the project.